Lovesick Ellie. 12 - Fujimomo (New York : Kodansha Comics, 2023)
At her high school, she's Eriko Ichimura, the girl so boring no one remembers she exists. But online, she's "Lovesick Ellie," a brash and lusty alternate persona with quite a viral following! Ellie's favorite pastime? Spying on her handsome and perfect classmate Ohmi and spinning wild fantasies in the form of very thirsty tweets. But one day, quite by accident, Eriko learns that Ohmi isn't as perfect as she thought...and he discovers her secret to boot!